IMMU-26. UNRAVELING ANTIGEN PRESENTATION IN CENTRAL NERVOUS SYSTEM ANTI-TUMOR IMMUNITY. (9th November 2020) - Bowman-Kirigin, Jay; Kobayashi, Dale; Livingstone, Alexandra; Saunders, Brian; Schaettler, Max; Liu, Connor; Durai, Vivek; Bowman-Kirigin, Jay; Leuthardt, Eric; Kim, Albert; Zipfel, Gregory; Osbun, Joshua; et al.
Abstract: The antigen presenting cell that primes T cells in the central nervous system (CNS) remains unknown. Outside the CNS, the conventional dendritic cell 1 (cDC1) subset presents antigen to and primes CD8 T cells. However, the steady-state CNS parenchyma is relatively devoid of all dendritic cell subsets, including cDC1. cDC1 are required for anti-tumor immunity a variety of other tumor types, but their role CNS tumors remains undefined. Using the orthotopic preclinical glioblastoma models, GL261 and CT2A, we characterized the role of cDC1 in the CNS anti-tumor immune response. While cDC1 are absent in the steady state brain, tumor presence drove recruitment of cDC1 into extravascular spaces within the tumor and adjacent brain parenchyma. We further found that while GL261-bearing wildtype mice experienced survival benefit following anti-PDL1 checkpoint blockade treatment, mice with cDC1 genetically deleted experienced no survival benefit. cDC1-deficient mice completely lacked neoantigen-specific CD8 T cells against the endogenously-primed GL261-neoantigen mutant Imp3, and possessed broad CD8 effector T cell defects compared to wild type mice. Furthermore, using a fluorescent tumor-associated reporter, we detected tumor-derived material within dendritic cells from the tumor, the lymphatic vessel-containing dura, and the cervical lymph nodes. We observed the human cDC1-equivalent CD141+ cDC within human brain tumors (not limited to GBM) and dura as well. We used the GBM-specific reporter, 5-aminoilevulinic acid/protoporphyrin IX (PPIX) fluorescent metabolite to resect the tumor, and observed PPIX specifically in conventional dendritic cell subsets that had infiltrated the resected tumor, but not within those same cell subsets in the periphery, nor in T cells within the tumor. These findings comport with the canonical understanding that cDC1 uptake antigen at the effector site and migrate to draining lymph nodes to prime effector CD8 T cells, and highlight the significant role that cDC1 play in CNS anti-tumor immunity in mice and humans.